Analysis of socio-economic factors influencing caesarean section rates in Maharashtra, India - Khadse, Rushikesh Premdas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The aim of the present study is to investigate the socio-demographic and economic determinants of caesarean (C-) section deliveries in Maharashtra. The paper also focuses to estimate inequalities in C-section deliveries in the state. Methods: The fifth round of the National Family Health Survey (NFHS) 2019-21 was used to accomplish the objective. Univariate, bivariate and logistic regression were used to ascertain the determinants of C-section. Results: The prevalence of C-section delivery in India rose from 2.9% during 1992-93 to 10.6% in 2005-06 and to 21.5% during 2019-21. The proportion of C-section delivery in Maharashtra during 2019-21 is observed to be 25.4%, with 18.3% of the deliveries occurring at public health facility, while 38.9% of the deliveries takes place in private health care settings. Women residing in urban areas, belonging to richer wealth asset index and having higher educational qualification are found to have greater chance of caesarean deliveries. Conclusions: The study reveals that C-sections have increased dramatically in Maharashtra over the previous three decades. The hospital administration is encouraged to take effective actions to reduce the likelihood of needless C-sections while retaining medical justification for C-section births.